Chinese Female Drug Users' Experiences and Attitudes With Institutional Drug Treatment - Liu, Liu (International journal of offender therapy and comparative criminology, 2018)
With its rapid economic growth and the increased influence of Western culture, China has become a drug-consuming country. Forty-six semistructured interviews were conducted in a compulsory drug treatment institution to document Chinese female drug users' experiences with and attitudes toward two mandated treatment modalities: vocational training and educational activities. Detainees required to participate in first institutional treatment showed enthusiasm and had more positive attitudes; those who had entered the compulsory treatment facilities 2 or more times generally had a negative outlook on their pursuit of abstinence. Although female detainees achieved detoxification in the institution, many relapsed upon release to their community, indicating the institutional compulsory treatment model's failure to ensure long-term abstinence. By revealing four main flaws of the current institutional compulsory treatment, this study indicates the need for a comprehensive treatment system that combines improvements to institutional treatment and development of community-based treatment to address different stages of abstinence.